![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
2个回答
展开全部
f'(-x)+xf'(x)=x 1)
以-x代入等式中的x,得:f'(x)-xf'(-x)=-x 2 )
1)*x+2),消去f'(-x),得:f'(x)(x^2+1)=x^2-x
即f'(x)=(x^2-x)/(x^2+1)=1-(x+1)/(x^2+1)
积分:
故f(x)=x-∫xdx/(x^2+1)-∫dx/(x^2+1)=x-0.5∫d(x^2)/(x^2+1)-arctanx
=x-0.5ln(x^2+1)-arctanx+C
以-x代入等式中的x,得:f'(x)-xf'(-x)=-x 2 )
1)*x+2),消去f'(-x),得:f'(x)(x^2+1)=x^2-x
即f'(x)=(x^2-x)/(x^2+1)=1-(x+1)/(x^2+1)
积分:
故f(x)=x-∫xdx/(x^2+1)-∫dx/(x^2+1)=x-0.5∫d(x^2)/(x^2+1)-arctanx
=x-0.5ln(x^2+1)-arctanx+C
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询